Contaminated land investigation, assessment and remediation - Harris, Mary (ICE design and practice guides., 1994)
This guide addresses the topics of investigation, assessment and remediation of contamination in the context of current thinking on how best to deal with the issues surrounding contaminated land, both in terms of redevelopment and from considerations of human health and environmental impacts.